FORMULASI MASKER CLAY EKSTRAK WORTEL DAN TEPUNG BERAS - Hasibuan, Elmi Sariani; Nasution, Dina Rahmi Solihad (Jurnal Kesehatan Ilmiah Aufa Royhan, 2023)
Dry skin is problematic skin, skin with insufficient and low water content. One easy and practical way to overcome this is to carry out cosmetic treatments using a clay mask with a formulation of carrot extract and rice flour. This research aims to obtain a clay mask preparation from carrot extract and rice flour. Carrot extract contains beta-carotene which is useful for protecting the skin from UV rays and is also rich in vitamin A and antioxidants which are very good for making skin brighter. Meanwhile, rice flour can help improve skin structure thanks to its abundant nutritional content, one of which is vitamin B and can help overcome external pollution and dirt and make skin look brighter. The ethanol extract of carrots and rice flour is formulated in the form of a clay mask with various extract formulations, namely 20%, 25% and 30%. The results of organoleptic testing, physical properties and stability tests of the mask preparations showed that no changes occurred in each formula, namely color, odor and shape during the storage process. All formulations obtained were homogeneous, the average pH was 5.58-6.73, the average spreading power obtained was 3.08-4.7 cm, the average sticking power obtained was 0.82-4.86 seconds, and the average -The average dry preparation produced was 6.21-19.02 minutes. The conclusion of this research is that carrot extract and rice flour can be formulated as a clay mask and are also stable during storage.